Demographic, Clinical and Microbiological Characteristics of Maternity Patients: A Canadian Clinical Cohort Study. (1st October 2002) - Wenman, Wanda M; Tataryn, Ivanna V; Joffres, Michel R; Pearson, Rachelle; Grace, Michael GA; Albritton, William L; Prasad, Errol; The Edmonton Perinatal Infections Group,
Abstract : OBJECTIVE: To determine the demographic, clinical and microbiological characteristics of a representative Canadian obstetrical population. DESIGN: A one-year cohort study of all maternity patients who were followed to delivery, using detailed patient questionnaires containing more than 60 demographic and clinical variables, and three microbiological evaluations during gestation - first trimester, 26 to 30 weeks, and labour and delivery. Outcome measurements included birth weight and gestational age. SETTING: Labour and delivery suites of all office obstetrical practices affiliated with a single hospital. POPULATION STUDIED: A consecutive sample of pregnant women in the study practices during one year were eligible for enrolment; 2237 consecutive patients were approached for consent, 2047 enrolled and 1811 completed the study through delivery. RESULTS: The average patient was white, married and 29 years of age. Slightly more than half of the patients had postsecondary education, but 10% fell below the national poverty line for income. Frequency of factors linked to adverse pregnancy outcomes included cigarette smoking (19%), alcohol ingestion (18%), previously having had a premature infant (7%), and maternal diabetes (2%). Overall prevalence of genital microbes variously implicated in prematurity was 37% for ureaplasma, 11% for group B streptococcus and 4% for Mycoplasma hominis . Prevalence of bacterial vaginosis was 14%. The median gestational age for the cohort was 39 weeks, with 7% of infants born less than 37 weeks' gestation. Mean birth weight was 3415 g. CONCLUSIONS: The present clinical cohort represents demographic and medical characteristics of the Canadian obstetrical population. The birth outcomes are consistent with national data. This database provides valuable information about a general obstetrical population that is managed by a universal health care system.